First results of archaeobotanical analysis from Neolithic layers of Buran Kaya IV (Crimea, Ukraine). (August 2015) - Salavert, Aurélie; Messager, Erwan; Motuzaite-Matuzeviciute, Giedre; Lebreton, Vincent; Bayle, Grégory; Crépin, Laurent; Puaud, Simon; Péan, Stéphane; Yamada, Masayoshi; Yanevich, Aleksander
Abstract : This paper contributes to understand the palaeoenvironment and the exploitation of vegetal resources during the Mid-Holocene in the southern Crimean Mountains. To address these questions, we apply a multi-proxy approach based on charcoal, seeds/fruits and phytoliths analyses from Neolithic layers (5800–5300 cal BC) of Buran-Kaya IV, a rock-shelter located in the south of Crimean Peninsula. Charcoal analysis shows that the Neolithic groups have exploited the Quercus petraeae forest belt composed mainly of Quercus, Carpinus and Acer. The identification of Fagus and a fragment of gymnosperm, which developed in upland areas, suggests the mobility of inhabitants of BK IV. According seed and phytolith analyses, it is more likely that the Neolithic groups did not practice agriculture on the site, and that their diet was not based on crop production. Furthermore, considering the probable absence of domestic animals in the layer 2, the economy may essentially be based on hunting-gathering at Buran Kaya IV.